On the Anticompetitive Effect of Exclusive Dealing when Entry by Merger is Possible - Chiara Fumagalli; Massimo Motta; Lars Persson (Research Institute of Industrial Economics (IFN), 2007)
We extend the literature on exclusive dealing, which assumes that entry can occur only by installing new capacity, by allowing the incumbent and the potential entrant to merge. This uncovers new effects. First, exclusive deals can be used to improve the incumbent's bargaining position in the merger negotiation. Second, the incumbent finds it easier to elicit the buyer's acceptance. Third, exclusive dealing, despite allowing the more efficient technology to find its way into the industry, reduces welfare because (i) it may trigger entry through merger whereas independent entry would be socially optimal, (ii) it leads to a sub-optimal contractual price when the exclusive dealing include a price commitment, (iii) it may deter entry altogether.
Keywords: L24; L42; 330; Technology Transfer; Inefficient Entry; Antitrust; Authority's Behavior; Monopol; Wettbewerb; Markteintritt; Fusion; Nachfragemacht; Technologietransfer; Theorie